Designing a scale for some personality traits of tennis, badminton and squash players for students of the College of Physical Education / University of Baghdad - Mahmoud Jassim, Ghada; Qassem Badr, Mohamed (International Journal of Psychosocial Rehabilitation, 2020)
The present study aimed to study some personality traits by measuring personality traits with the Freiburg scale on a sample of students of the College of Physical Education/University of Baghdad who specialize in the games concerned with the research. In order to achieve the goal of the research, the researcher designed the rate scale to measure some personality traits after ensuring the validity and stability of the scale in the research community, and after processing the data and information obtained by statistical methods, the researcher reached the results that characterized the sample groups in the characteristics of the researcher, and it was noticed that the neurotic feature had higher values than other traits. The research community consisted of a group of students of the College of Physical Education/University of Baghdad, who were (22) students out of (26), and they were divided into three groups according to the aforementioned games, which the scale was applied to them with the research. The researcher concluded that the psychological aspect is an important and influential factor in the sports field in terms of good performance and better achievement of goals. The researchers recommend, through the findings of a mechanism, the study of the personality traits of each student and in depth in this area, as it is the main reason for the progress and decline of performance.